Mistake of Fact or Mistake of Criminal Law? Explaining and Defending the Distinction - Simons, Kenneth W. (Criminal law and philosophy, 2009)
This article makes six points. First, under any plausible normative perspective, the distinction between mistake (and ignorance) of criminal law and mistake of fact must at least sometimes be drawn. Second, the fundamental distinction is between a mistake about the state's authoritative statement of what is prohibited ( M Law ), and a mistake about whether that prohibitory norm is instantiated in a particular case ( M Fact ). Third, when an actor makes a mistake about an evaluative criterion whose content the fact-finder has discretion to elaborate, it is impossible both to allow this discretion and to faithfully realize a jurisdiction's policy of treating M Fact and M Law differently. Fourth, the claim that every unreasonable M Fact is really a M Law elides important differences between the two kinds of mistake. Fifth, various borderline objections, such as the famous Mr. Fact/Mr. Law example, do not undermine the fundamental distinction, although in rare instances, they do constitute genuine counterexamples that do not effectuate the principles and policies that the distinction ordinarily serves; and even here, they are exceptions that prove (the rationale for) the rule. Sixth, specification or evolution of a criminal law norm, such as the criterion for nonconsent in rape law, can convert a legally relevant M Fact into a legally irrelevant M Law. This phenomenon does not undermine the fundamental distinction between these types of mistake; to the contrary, it reveals the significance of that distinction